An Analysis of Young Learners’ Enggagement toward Using Video Clips and Guided Practice in Teaching English: Examining the Teacher’s Point of View - Riza Amelia; Zelly Putriani (Milenial: Journal for Teachers and Learning, 2025)
This research examines the role of video clips and guided practice in enhancing young learners' engagement in English in Pekanbaru, Indonesia. Using a descriptive qualitative research design, the research aimed to do an analysis of young learner’s engagement toward using video clips and guided practice in teaching English from the teacher’s point of view as the creator of the learning. The data were collected through interview, classroom observations and focus group discussion. The participants of the research were one teacher, and fifteen students. The findings indicated that the teacher had constructed a careful plan to engage the young learners during the learning through using an integration of video clips that was coupled with guided practice in teaching English. Through triangulation, the teacher was observed to prioritizing young learner’s engagement through interactive and appropriate videos, providing clear guidance during practice activities, and incorporating student feedback. Overall, the teacher could create a dynamic and supportive learning environment. However, challenges remain, whereas there were a few students not fully participated. Future research is suggested to focus on examining the specific strategies that the teachers can employ when integrating video clips and guided practice and exploring the impact on young learners' long-term learning engagement.